EVOLUTION OF METHODS OF STOPPING BLEEDING FROM THE PRESACRAL VENOUS PLEXUS IN PELVIC SURGERY: A REVIEW OF THE LITERATURE - E. M. Parfireva; A. O. Ivchenko; O. A. Ivchenko; A. V. Avgustinovich (Сибирский онкологический журнал)
The purpose of the study was to analyze various methods of stopping bleeding from the presacral venous plexus.Material and Methods. Literature search was carried out using Elibrary, Medline, Embase databases from January 1960 to November 2018.Results. Bleeding from the presacral venous plexus is a rare but potentially life-threatening complication in pelvic surgery. The inferior vena cava, the veins of the presacral and internal spinal plexuses are dilated under general anesthesia, and act as a large venous “blood pool” in the pelvis because of the lack of functional valves. Hydrostatic pressure in this venous pool can reach two to three times the pressure of the inferior vena cava. Thus, rupture of even a small presacral vein may result in heavy bleeding. Among the many reported methods of stopping this bleeding, the most effective are as follows: mechanical tamponade; technique of pressing the bleeding site; ectrocoagulation; the use of hemostatic materials.Сonclusion. The variety of methods used for stopping bleeding from the presacral venous plexus indicate a need of searching for more effective methods.